2013
DOI: 10.1093/ije/dyt002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy overweight and obesity, and child neuropsychological development: two Southern European birth cohort studies

Abstract: This study in two birth cohorts with moderately high obesity prevalence suggests that maternal pre-pregnancy obesity is associated with reduced child cognitive development at early ages. This association appears more likely to be due to maternal than shared family and social mechanisms, but further research is needed to disentangle a direct intrauterine effect from other maternal confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
96
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 27 publications
6
96
0
5
Order By: Relevance
“…13 The study also found an inverse association with cognitive scores. 13 However, our findings do not support a previous US study on maternal obesity. Specifically, at 2 years (n = 6850), the study found by guest on March 28, 2019 www.aappublications.org/news Downloaded from no association with psychomotor development (encompassing fine and gross motor) but observed a relation with delayed mental development.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…13 The study also found an inverse association with cognitive scores. 13 However, our findings do not support a previous US study on maternal obesity. Specifically, at 2 years (n = 6850), the study found by guest on March 28, 2019 www.aappublications.org/news Downloaded from no association with psychomotor development (encompassing fine and gross motor) but observed a relation with delayed mental development.…”
Section: Resultsmentioning
confidence: 71%
“…13 Psychomotor scores (and only those reflecting fine motor) were inversely associated with maternal BMI and not for paternal BMI. 13 The study also found an inverse association with cognitive scores. 13 However, our findings do not support a previous US study on maternal obesity.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Gross motor function is the process of developing from head to legs; after a child is able to keep his head upright and control the shoulder muscles and trunk, the child will be able to control his or her legs [1,2]. Fine motor function develops from proximal to distal direction.…”
Section: Introductionmentioning
confidence: 99%
“…Each new motor skill is acquired in a specific order that is dependent on that which has been developed earlier; for example, first a child learns to support his or her body weight, then that child will begin to stand and later walk. It's very important to learn all the movements from the beginning; it is the basis for all other, more complex movements [1,2].…”
Section: Introductionmentioning
confidence: 99%